Zoonotic Giardia duodenalis Genotypes and Other Gastrointestinal Parasites in a Badger Population Living in an Anthropized Area of Central Italy - Michela Maestrini; Federica Berrilli; Alessia Di Rosso; Francesca Coppola; Isabel Guadano Procesi; Alessia Mariacher; Antonio Felicioli; Stefania Perrucci (Pathogens, 2022)
The Eurasian badger (Meles meles) is widespread in Italy and occupies different habitats. The occurrence and species of gastrointestinal parasites were evaluated in a free-ranging badger population living in a highly anthropic area in central Italy. A total of 43 fecal samples were examined using the flotation test, the Mini-FLOTAC and Baermann techniques, and a rapid immunoassay for the detection of Giardia duodenalis and Cryptosporidium spp. fecal antigens. Molecular investigations were also performed that aimed at identifying Giardia genotypes. Overall, 37/43 samples (86%) were found positive. Specifically, 48.8% (21 samples) were positive for G.duodenalis, 23.2% (10/43) for Cryptosporidium spp., and 7% (3/43) for coccidian oocysts. Strongyloides sp. nematode larvae were detected in 3/43 samples (7%). Ascarid (1/43, 2.3%), capillariid (1/43, 2.3%), and strongyle-type eggs (76.7%, 33/43) were also identified. Among the 11 readable sequences of samples that were positive for G. duodenalis by end-point PCR (18/21), the zoonotic assemblage A sub-assemblage AII and mixed assemblage A and B were identified. This is the first report of zoonotic G. duodenalis genotypes in the Eurasian badger. Moreover, most of identified parasites have zoonotic potential and/or potential impact on the population health of wild badgers and other wild and domestic animals.